2021
DOI: 10.5534/wjmh.190112
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Predict a Successful Outcome after Varicocelectomy in Painful Varicocele Patients? An Updated Meta-Analysis

Abstract: Chronic scrotal pain is defined as chronic or intermittent scrotal pain of at least 3 months, with various levels of severity, that interferes with daily activities and prompts the patient to seek medical treatment [1]. Common causes of scrotal pain include varicocele, epididymitis, spermatocele, tumors, infection, and torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Hence, further prospective randomized studies are required. Moreover, some studies have reported subinguinal ligation and microsurgical varicocelectomy as more effective in relieving varicocele-associated pain than other surgical techniques [ 20 , 21 ]. However, in our study, we adopted only the gold standard microscopic subinguinal approach [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, further prospective randomized studies are required. Moreover, some studies have reported subinguinal ligation and microsurgical varicocelectomy as more effective in relieving varicocele-associated pain than other surgical techniques [ 20 , 21 ]. However, in our study, we adopted only the gold standard microscopic subinguinal approach [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients with bilateral varicoceles have two different varicocele grades, there was an uneven distribution of patients for the varicocele grade, creating a potential for bias. In addition, not including other predictive factors such as various surgical techniques, varicocele location, and number of ligated veins could have potentially affected the pain resolution and success rate after varicocelectomy [ 9 , 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic varicocelectomy was found to be superior to the laparoscopic approach in terms of surgical outcomes ( p < 0.0001) [ 30 ]. Furthermore, due to its inability to reach the external gonadal vessels or external spermatic veins [ 31 ], laparoscopic varicocelectomy was reported to have a higher recurrence rate (17.2%, 34 of 198 patients) compared with microsurgical and open nonmicrosurgical methods [ 32 ].…”
Section: Diagnosis and Gradingmentioning
confidence: 99%
“…To the best of our knowledge, there has been little research about predictive factors for surgical outcomes in patients with painful varicocele [ 2 ]. We have carefully read the article published in the World Journal of Men's Health by Park et al [ 3 ], and the findings are indeed interesting. This article, a meta-analysis of 14 trials, addresses the relationship between varicocele characteristics and surgical methods and the pain resolution rate following varicocelectomy.…”
mentioning
confidence: 99%
“…This article, a meta-analysis of 14 trials, addresses the relationship between varicocele characteristics and surgical methods and the pain resolution rate following varicocelectomy. Patients with varicocele preoperatively complaining of dull pain demonstrated a higher likelihood of postoperative pain resolution than those complaining of excruciating or sharp pain [ 3 ]. These results may help in choosing a proper treatment method for patients with painful varicocele.…”
mentioning
confidence: 99%